Eficiência de fungos e bactérias para o controle do percevejo-marrom (Euschistus heros) na soja (Glycine max) - (:unkn) unknown (Universidade Federal do Pampa, 2024)
Brazil is the world's largest producer and exporter of soybeans (Glycine max) and in the 2023/2024 harvest, an area of 45.7 million hectares was produced. Stink bugs are among the main insect pests that attack the crop, causing irreversible and significant damage to seed quality and yield through poor formation of legumes and grains. The brown stink bug (Euschistus heros) can be cited as one of the three main species that attack soybeans, leading to the need to control this insect. The objective of this study was to conduct a literature review to evaluate the efficiency of the fungi Beauveria bassiana, Metharizium anisopliae and the bacteria Bacillus subtilis and Bacillus thuringiensis in the mortality rate of the brown stink bug. Tests performed with Metarhizium anisopliae generally showed a shorter time for insect mortality. The results in controlled environments were encouraging, but more field tests are needed, since fungi and bacteria can behave differently due to management practices or the climate in the area.
Efficiency of fungi and bacteria for the control of brown stink bug (Euschistus heros) in soybean (Glycine max)
Keywords: Insetos praga; Controle biológico; Entomopatógenos; Insect pests; Biological control; Entomopathogens; CNPQ::CIENCIAS AGRARIAS